中学生男子におけるジャンプ能力の評価: 陸上競技クラブチームのメンバーと非メンバーを対象とした研究 - 林, 陵平; 藤澤, 慶己; 日置, 佑輔 (コーチング学研究, 2025)
This study aimed to determine the double- and single-leg jumping abilities of junior high school track and field club team members versus non-members. Thirty-six track and field club team members and 40 non-members (all aged 13-15 years) were included. Countermovement jump (CMJ), rebound jump (RJ), single-leg CMJ (SCMJ), and single-leg RJ (SRJ) moves were performed on a mat switch. RJ index and jump heights for CMJ, SCMJ, RJ, and SRJ were calculated. All variables except SRJ-index, RJ and SRJ jump heights for first-year junior high school students, CMJ and SCMJ jump heights for second-year junior high school students, and CMJ jump height for third-year junior high school students were significantly higher in track and field club members than in non-members (p < 0.05). The RJ and SRJ ground times were also significantly lower in junior high school students who belonged to a track and field club team than in those who did not (p < 0.05). These results suggest that junior high school students belonging to track and field club teams have better double and single-leg treadmill jumping abilities than those who do not. Therefore, an improvement in the lower limb stretch-shortening cycle performance equal to or greater than that observed with track and field club activities can be expected through activities in a track and field club team.